Barriers and facilitators in nurse prescribing practices: a protocol for qualitative meta-synthesis from nurses’ perspectives - Hui Luo; Xin Zhou; Cheng Lei; Kejimu Sunzi; Yadi Li (BMJ Open)
Introduction With the development of the medical system and the diversification of patient needs, nurse practitioners (NPs) play an increasingly important role in medical practice, assuming more responsibilities and powers, including the right to prescribe. However, in the process of exercising the right to prescribe, NPs may face various obstacles, and there are also some promoting factors. Therefore, this study aims to deeply explore the obstacles and promoting factors in the prescription process of NPs through a qualitative meta-analysis and comprehensive method, so as to provide a basis for improving the prescription practice of NPs, improving nursing quality and patient satisfaction.Methods and analysis This study will adhere to the Joanna Briggs Institute framework and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. A comprehensive literature search and analysis of studies on nurse are prescribed via PubMed, Embase, Web of Science, CINAHL and the Cochrane Library. Two independent reviewers will select articles, extract data and appraise study quality. Content analysis will be used to synthesise outcomes, and methodological quality and evidence quality will be assessed. The quality of the articles will be assessed using the 10-item Joanna Briggs Institute Critical Appraisal Checklist for Qualitative Research.Ethics and dissemination Ethical approval will not be required for this study, as it solely encompasses data derived from previously published research. The findings will be disseminated through publication in a peer-reviewed journal. In addition, the results will be actively shared at major academic conferences focused on nursing research and healthcare policy to ensure that the study’s outcomes reach key stakeholders, including healthcare practitioners, policymakers and researchers. This targeted dissemination strategy aims to promote the integration of the findings into practice and future research. This protocol is registered with the PROSPERO prospective database of systematic review.PROSPERO registration number CRD42023398567.